Provenance Analysis of the Late Ediacaran Basins from Southwestern Iberia (Série Negra Suecession and Beiras Group): Evidence for a Common Neoproterozoic Evolution - Lopes, Luís (2015)
This study makes a comparison of detrital-zircon age populations from upper Ediacaran greywackes of the Ossa–Morena Zone (OMZ) with those from the southern domains of the Central Iberian Zone (S-CIZ). The results reveal that the main difference between the age spectra of both populations of detrital zircon is the Neoproterozoic, in particular the Cryogenian grains. Our new data suggest that deposition in the CIZ and OMZ Ediacaran basins was coeval, indicating a long-lived magmatic event typical of the northern Gondwana margin (Avalonian–Cadomian belt and Pan-African belt). Overall, southwestern Iberia shows the following sequence of Cryogenian and Ediacaran zircon-forming events: (1) ca. 850–700 Ma, Pan-African suture (well represented in the Beiras Group and in the Mares Formation of the Série Negra succession); (2) ca. 700–635 Ma, early Cadomian arc (dominant in the Beiras Group and in the Mares Formation of the Série Negra succession); and (3) ca. 635–545 Ma, late Cadomian arc (predominant in the Mosteiros and Escoural formations of the Série Negra succession). The results emphasise that the late Ediacaran basins of southwestern Iberia evolved together in the active margin of North Gondwana in the same palaeogeographical scenario but were sufficiently separated to justify the differences identified in their Neoproterozoic detrital zircon contents. This finding shows that there is no basis for considering that the boundary between the OMZ and the S-CIZ marks a Cadomian suture.